Art therapy in pediatric burn care: A conceptual framework for clinical practice. Issue 7 (November 2022) - Malhotra, Bani; Kaimal, Girija
Highlights: Art therapy conceptual framework for 3 stages of burn treatment- critical, acute, and rehabilitation is presented. Framework is based on narrative synthesis of research on psychosocial needs of burn-injured children and art therapy. Art therapy can support pediatric burn recovery as a psychosocial intervention for short-term and long-term goals. Abstract: Burn injuries are an unexpected traumatic event and can be physically and emotionally devastating for a child and their families. This article presents a conceptual framework for art therapy practice with pediatric burns, founded on the three stages of burn treatment- critical, acute, and rehabilitation. The framework is based on narrative synthesis of research on the psychosocial needs of children with burn injuries, art therapy literature on pediatric burn patients, as well as in medical settings. Based on the stages of burn recovery, and the role of other relevant stakeholders, the framework provides recommendations for clinical practice of art therapy with children sustaining burn injuries, their caregivers and siblings, and healthcare providers. Robust studies including art therapy as interventions are recommended to determine their effectiveness in addressing the specific psychosocial needs in different stages of pediatric burn care.